Executive stock options, differential risk-taking incentives, and firm value - Armstrong, Christopher S.; Vashishtha, Rahul (Journal of Financial Economics, 2012)
The sensitivity of stock options' payoff to return volatility, or vega, provides risk-averse CEOs with an incentive to increase their firms' risk more by increasing systematic rather than idiosyncratic risk. This effect manifests because any increase in the firm's systematic risk can be hedged by a CEO who can trade the market portfolio. Consistent with this prediction, we find that vega gives CEOs incentives to increase their firms' total risk by increasing systematic risk but not idiosyncratic risk. Collectively, our results suggest that stock options might not always encourage managers to pursue projects that are primarily characterized by idiosyncratic risk when projects with systematic risk are available as an alternative.